Could Artificial Neurons Create a Neural Plasticity of Their Own? - Namaki , M. S. S. El (Advanced Research in Biological Science Vol. 2, 2023)
This chapter explores the tenants of biological neurons and their plasticity. It then proceeds with an analysis of artificial neurons and the potential for artificial neural plasticity. Artificial neural plasticity is then placed within the context of strategic thinking. A conceptual framework is then attempted. Neural plasticity is the brain’s capacity to restructure its performance and function along biological, chemical, and physical lines. It is the source of structural changes in brain functions and performance. It could be functional but it could also be structural. The process is driven by three forces: learning, experience and memory or as a result of trauma. It is created during different phases of an individuals’ life time. Early childhood creates a core and subsequent life phases enhance and complement this core. Current work on artificial intelligence attempts, more frequently than not, to simulate human brain process. Those include neural plasticity. And the question could arise: could an artificial neurons system or group of systems develop their own neural plasticity? And how and for what purpose? The article could provide a step forward in the question whether AI could progress to the so called “self-awareness” phase. Self-awareness assumes a measure of neural plasticity, a fundamental dimension of a fully developed AI.